Graecia Belgica: writing Ancient Greek in the early modern Low Countries. (17th March 2022) - Lamers, Han; Van Rooy, Raf
Abstract: The early modern Low Countries formed a multilingual region where Latin and several vernaculars lived in symbiosis. It is often forgotten, however, that Ancient Greek was also cultivated among the cultural and intellectual elite, so intensely that a vast corpus of Greek texts was produced in this region. This article offers a first exploration of the reasons behind this cultural phenomenon. It starts with a general introduction, including a state of research in the field and a first survey of the source materials. The main body of the article is divided into two parts. The first situates the so-called New Ancient Greek literature of the early modern Low Countries in historical perspective by introducing first Greek studies and then Greek composition in this region. Against this background, the second part explores what motivated and inspired this Greek literary production in four sections, each discussing an important aspect of the phenomenon under study: language learning, cultural distinction, networks and communities, and aesthetic appreciation. The article thus demonstrates that writing in Greek in the early modern era had uses far beyond showing off one's literary talent and erudition.